Tadalafil Preserves Penile Nitric Oxide Synthase from Detrimental Effect of Paroxetine in Rats - KABASAKAL, LEVENT (AVES, 2019)
Objective: Paroxetine is a commonly prescribed SSRI that can impair erectile function in animal models via inhibition of nitric oxide synthase (NOS). Tadalafil potentiates nitric oxide (NO)-mediated responses in isolated trabecular smooth muscle and penile erection. The purpose of this study was to evaluate the impact of co-administering tadalafil with paroxetine on penile NOS levels in rats. Materials and Methods: A total of 30 male Sprague-Dawley rats were divided into 3 groups as control (Group-C), paroxetine (Group-P) and paroxetine plus tadalafil (Group-P+T). After 28 days of treatment, rats were sacrificed and their penile tissues were harvested for analysis. NOS isoform protein levels and immunoreactivity scores of NOS were assessed. Statistical significance level was set at p<0.05. Results: Neuronal NOS (nNOS) levels were significantly decreased in group-P, compared with group-C (p<0.001). In comparison, rats in group-P+T had significantly higher nNOS levels compared to group-P (p<0.001). Endothelial NOS (eNOS) and inducible NOS (iNOS) levels were significantly higher in group-P compared with group-C (p<0.01). The levels of eNOS and iNOS in group-P+T were similar to group-C. Conclusion: Daily treatment with tadalafil prevented chronic paroxetine-induced changes in all three NOS isoform levels. Tadalafil treatment may therefore be a useful therapy in men with paroxetine-associated erectile dysfunction.
Keywords: Erectile dysfunction; tadalafil; paroxetine; nitric oxide; rat; SEROTONIN REUPTAKE INHIBITORS; MENTAL-DISORDERS; EXPRESSION; PATTERNS